New Drugs on the Horizon to Treat MDR Pathogens - Butterman, Eric (MD Conference Express, 2011)
Aminoglycosides are a well-known class of drugs with proven efficacy; however, they are being used less frequently because of resistance, nephrotoxicity, and ototoxicity. This article discusses plazomicin (formerly ACHN-490), a new aminoglycoside that is used to treat gram-negative infections.